Stock Price Valuation After Issue of The Indonesian Islamic Bank Merger Breakup - Versiandika Yudha Pratama (Banque Syar'i: Jurnal llmiah Perbankan Syariah, 2023)
Stock price valuation is the process of assessing the share price of a company that aims to determine the intrinsic value or fair value of the company. This research is a study that aims to determine the intrinsic value of BRIS companies using a relative valuation approach which is then analyzed using two methods, namely Price Earning Ratio (PER) and Price to Book Value (PBV). This research can serve as a source of information that can assist in making investment decisions through a comparison between market prices and fair prices. This research is included in the category of quantitative descriptive research that uses secondary data as a source of information in the form of historical data obtained from www.stockbit.com. The data used are stock prices for the last 5 years, Earning Per Share data (current EPS) and mean PER data, as well as current book value per share data (current BVPS) and mean PBV. The results showed that the BRIS company valued using the PER method is included in the cheap category (undervalued) so investors are recommended to invest their funds in these shares, while when valued using the PBV method shows that the BRIS company is included in the overvalued category because the market price is greater than the fair price. However, the difference between the fair price and the share price is only small so investors are advised to keep buying the shares.